STEAM power : infusing art into your STEM curriculum (International society for technology in education, 2020)
"There are numerous books on STEAM, but most are either arts and crafts project books designed for children or high-level books that can be weighty and inaccessible for new teachers. As an artist/educator who has taught art and technology for years, Tim Needles brings a fresh and unique approach to these topics, focusing on creativity, innovation and collaboration. This accessible and engaging book offers creative ideas for blending arts and STEM learning (STEAM). It covers the fundamentals of STEAM, with project ideas and best practices, while providing insight from educators in the field. Technologies covered include: coding, robotics, 3D printing, virtual and augmented reality, photography, video, animation and digital drawing. In addition, the book addresses several different approaches to bringing STEAM learning to the next level, such as collaboration, global learning, project-based learning, makerspaces and social-emotional learning"--